2013
DOI: 10.1016/j.electacta.2013.03.158
|View full text |Cite
|
Sign up to set email alerts
|

Parylene C coated microelectrodes for scanning electrochemical microscopy

Abstract: a b s t r a c tHerein, we present a simple microelectrode preparation methodology consisting in coating a platinum wire or a carbon fiber with a thin insulating Parylene C film (e.g. 1-10 m), to produce SECM probes with a small and constant probe RG (i.e. ratio between the radius of the insulating sheath and the radius of the active electrode area). After exposition of a fresh active electrode area by blade cutting, a disc shaped electrode is obtained thanks to a protective hot mounting wax layer that avoids P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…Parylene-C was selected due to its high dielectric property, biocompatibility, pin-hole free and uniform coatings, and its common use for neural prostheses. [41] Microelectrodes made from bare graphene microfiber (i.e., no Pt coating) were fabricated for comparison (Figure S3). Moreover, while the polymer coating process increased the robustness of the graphene microfibers, the flexibility was also improved as demonstrated by tying an overhand knot (Movie 1 and Figure S4).…”
Section: Microelectrode Fabricationmentioning
confidence: 99%
“…Parylene-C was selected due to its high dielectric property, biocompatibility, pin-hole free and uniform coatings, and its common use for neural prostheses. [41] Microelectrodes made from bare graphene microfiber (i.e., no Pt coating) were fabricated for comparison (Figure S3). Moreover, while the polymer coating process increased the robustness of the graphene microfibers, the flexibility was also improved as demonstrated by tying an overhand knot (Movie 1 and Figure S4).…”
Section: Microelectrode Fabricationmentioning
confidence: 99%
“…Conformal Parylene film is a good insulator on 3D electrodes, and it can be easily patterned by O 2 plasma etching. [115,116,[118][119][120] Due to these characteristics, Parylene can be applied as an insulation layer on entire devices, [116,119,121] or as a substrate of free-standing 3D probes. [79,117,122,123] Figure 7b shows an SEM image of a microelectrode coated with Parylene-C. [124] Ghame-Motlagh et al reported that Parylene-C were deposited using a chemical vapor deposition process and etched by oxygen plasma from the tips.…”
Section: Polymersmentioning
confidence: 99%
“…To equilibrate the chemical potentials of oxygen in the solution and across the interface, oxygen partitioning takes place and additional oxygen is supplied from across the interface, or from within the porous interface. For example, an oxygen partition induced positive feedback is observed when approaching a liquid‐air interface, [31] a water‐air interface,[ 32 , 33 ] or an interface with a porous hydrophobic film. [1] In these cases, the positive feedback is not due to the electrochemical reaction on an electrochemically active substrate, but positive feedback due to the availability and partitioning of the additional oxygen for equilibrating the chemical potentials of the oxygen in the solution and across the interface.…”
Section: Introductionmentioning
confidence: 99%